2016
DOI: 10.1097/sga.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Lived Experiences While Hospitalized After Surgery for Ulcerative Colitis

Abstract: Adolescents are in a transitional phase of life characterized by major physical, emotional, and psychological challenges. Living with ulcerative colitis is experienced as a reduction of their life quality. Initial treatment of ulcerative colitis is medical, but surgery may be necessary when medical treatment ceases to have an effect. No research-based studies of adolescents' experience of the hospital period after surgery for ulcerative colitis exist. The objective of the study was to identify and describe ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
9
0
7
Order By: Relevance
“…The thematic analysis commenced after four interviews had been completed and continued iteratively until data saturation was confirmed to have been reached [33] and where no new codes or themes were revealed. Due to the rich and detailed amount of data arising from the interviews we also deemed that ‘information power’ was sufficient to meet the study aims and objectives [24]. The transcripts were distributed to three qualitative researchers, one of whom was the primary researcher involved in data capture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thematic analysis commenced after four interviews had been completed and continued iteratively until data saturation was confirmed to have been reached [33] and where no new codes or themes were revealed. Due to the rich and detailed amount of data arising from the interviews we also deemed that ‘information power’ was sufficient to meet the study aims and objectives [24]. The transcripts were distributed to three qualitative researchers, one of whom was the primary researcher involved in data capture.…”
Section: Methodsmentioning
confidence: 99%
“…However, qualitative studies have considered: patient experience in relation to non-medical adaptation and non-medical intervention [21], disease burden [22], and a full review has been undertaken of generic meanings around living with inflammatory disease [23]. In addition, some qualitative studies have been undertaken relating to adolescent experience and those transitioning to early adulthood [24, 25], such as a study of adolescent hospitalization, and paediatric-provider relationships, as patients transition out of care settings. This gap is somewhat surprising given that qualitative methods are well suited to investigating personal experience in relation to drug taking or surgical intervention [26], and individual perceptions and belief and meaning systems [27, 28] and can help to clarify patients’ understanding of their disease and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that adolescents should have the opportunity to be accompanied by a parent or other attachment figure during hospitalization, to cope with the negative feelings that a hospital admission could bring. Previous studies have found that there is a lack of accommodation possibilities for parents in the pediatric wards ( Stremler, Adams, & Dryden-Palmer, 2015 ) or that adolescents are admitted to adult wards ( Dean & Black, 2015 ; Olsen et al., 2016 ). A clinical implication of our findings is that all children below the age of 18 always should be admitted to pediatric wards, organized to accommodate parents during their child’s hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adolescents described a lack of competence among the nursing staff in managing professional relationships with adolescents, leading to patronizing staff treating adolescents like small children ( Dean & Black, 2015 ). In another study, adolescents at adult wards expressed feelings of being out of place and that they missed the company of other young people ( Olsen, Jensen, Larsen, & Sorensen, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they experience low energy and, if surgery is required, adolescents may suffer from pain and bloody diarrhoea and are burned by anxiety. Some patients experience stomach pain, side effects such as weight gain or changes in facial form and acne before and/or after the intervention (38).…”
Section: Physical Needsmentioning
confidence: 99%